Effect of Boron on flower and fruit setting, and yield of ratoon Brinjal crop - Suganiya, S.; Kumuthini, D.H. (Eastern University, Sri Lanka, 2014)
This experiment was undertaken to study the effect of boron on flower and fruit setting, and yield of ratoon crop of brinjal (Solanum melongina L) in the Eastern region of Sri Lanka during the period January to March 2014, with the variety of brinjal ‘‘Thinnavelli purple.’’ The treatments were arranged in a Randomized Complete Design (RCBD) replicated three times. The treatments were defined as follows: T1-50 ppm, T2-100 ppm; T3-150 ppm and T4- Control along with recommended fertilizer. All other agronomic practices were in accordance with the Department of Agriculture. The results showed that foliar application of boron (H3BO3) at 150 ppm increased the number of flower buds/plant (70%), number of flowers/ cluster (141%), number of flower clusters/plant (48%), total number of flowers/plant (122%), Percentage of flower-set (30%), percentage of fruit-set (46%), number of fruits/plant (216%) and fresh weight of fruits/plant (88 %) than that of control. It was, therefore, concluded that foliar application of H3BO3 at150 ppm (at flowering stage) could increase flowering, fruit set percentage and fruit yield per plant of ratoon crop of brinjal in the regosol of Batticaloa district.
Keywords: Brinjal; Flower-set; Fruit-set